A Facility Siting Activist’s View - Dunning, Bob (Maine Policy Review, 1992)
The seeming paralysis in siting waste disposal facilities and other new facilities in Maine and other states underscores the difficulty of designing and implementing processes that will safeguard the environment and human health while sustaining economic development. Bob Dunning, a facility siting activist, offers some suggestions to government and industry officials on how to communicate better with facility siting opponents.